Acipenser baerii Brandt 1869 - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza (Zenodo, 2024)
3. Acipenser baerii Brandt, 1869 Common name. Siberian sturgeon Taxonomy. Original description: Acipenser baerii Brandt, 1869: 115 [Ob and Lena River systems, Siberia, Russia; syntypes: whereabouts unknown]. Revisions. Berg (1948: 86). Illustrations. Berg (1948: 86, fig. 66). Distribution in Iran. —Distribution in River Basin: Caspian Sea.—Distribution in Ecoregions: 434-Kura-South Caspian Drainages, 450-Turan Plain. Status in Iran. [Exotic].—Tas mahi baeri.—Listed in previous checklists from Iran by Esmaeili et al . (2017 a, 2018); Jouladeh-Roudbar et al. (2020) and Eagderi et al. (2022).—Iran material: None. Conservation. Not relevant (introduced species). Published as part of Sayyadzadeh, Golnaz & Esmaeili, Hamid Reza, 2024, Freshwater lamprey and fishes of Iran: Reappraisal and updated checklist with a note on Eagderi et al. (2022), pp. 1-99 in Zootaxa 5402 (1) on page 9, DOI:10.11646/zootaxa.5402.1.1, http://zenodo.org/record/10524097